2020
DOI: 10.1016/j.acra.2020.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Semiquantitative lung ultrasound scores in the evaluation and follow-up of critically ill patients with COVID-19: a single-center study

Abstract: Rationale and Objectives Chest CT is not suitable for critically ill patients with COVID-19 and lung ultrasound (LUS) may play an important role for these patients. In this study, we summarized the findings of LUS and explore the value of semiquantitative LUS scores in evaluation and follow-up of COVID-19 pneumonia. Materials and Methods Retrospectively studied the LUS and chest CT imaging of 128 critically ill patients with COVID-19. The imaging data were reviewed to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
56
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(75 citation statements)
references
References 21 publications
7
56
0
4
Order By: Relevance
“…Moreover, the correlation of total LUS score after 72 hours with ICU/death suggests that ultrasonographic monitoring accurately reflects disease progression. This result indicates the potential value of LUS as a tool for dynamic lung monitoring, thus extending what reported by Deng et al and Dargent et al [ 21 , 23 ] to a less critical population.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Moreover, the correlation of total LUS score after 72 hours with ICU/death suggests that ultrasonographic monitoring accurately reflects disease progression. This result indicates the potential value of LUS as a tool for dynamic lung monitoring, thus extending what reported by Deng et al and Dargent et al [ 21 , 23 ] to a less critical population.…”
Section: Discussionsupporting
confidence: 87%
“…To our knowledge this is the first prospective study assessing the potential role of LUS as a prognostic tool in a population of patients admitted to non-ICU units for COVID-19- related pneumonia. Zieleskiewicz et al and Deng et al showed that LUS scores highly correlated with CT scores [ 20 , 21 ]; moreover, the last study showed that the use of a score cut-off was able to distinguish between more and less severe critical patients. Lichter et al showed that LUS score at admission could accurately predict death and need for mechanical ventilation [22] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lung ultrasound score (LUS) is a semiquantitative score that measures lung aeration loss caused by different pathological conditions [ 18 , 19 ]. There are a few prospective studies demonstrating that lung ultrasound can predict outcomes in COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Lung ultrasound is widely used in Emergency Departments because it is user-friendly, broadly available, low-cost, and has high accuracy for diagnosing pulmonary diseases (17). Recent reports suggests that, in COVID-19 patients, lung ultrasound could be useful in several scenarios: to quantify severity of lung involvement in periodic assessments; to look for ndings suggestive of pneumonia; and to monitor the dynamic effects of mechanical ventilation and recruitment maneuvers on lung aeration (3,18). However, there are no prospective studies demonstrating that lung ultrasound can change management or predict outcomes in COVID-19.…”
Section: Introductionmentioning
confidence: 99%